Implementasi dan Pelaksanaan Terhadap Kode Etik Advokat Bagi Pelaku Hukum di Lembaga Peradilan di Indonesia - Sahid, Syarifuddin (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Implementation of the Advocate Code of Ethics for Legal Actors in Judicial Institutions in Indonesia This study aims to encourage the implementation and implementation of the Advocate Code of Ethics for legal actors in judicial institutions in Indonesia. The results of the study indicate that there are still several challenges in the implementation of this code of ethics, including a lack of understanding of the ethical standards that must be adhered to by advocates. This study also provides recommendations to increase awareness and awareness of the advocate code of ethics in judicial institutions in Indonesia